Interfacial layer thickness design for exploiting the reinforcement potential of nanocellulose in cellulose triacetate matrix. (28th July 2017) - Soeta, Hiroto; Fujisawa, Shuji; Saito, Tsuguyuki; Isogai, Akira
Abstract: The contribution of the interfacial layer thickness to composite properties was investigated using 2, 2, 6, 6-tetramethylpiperidine-1-oxyl (TEMPO)-oxidized cellulose nanofiber (TOCN) and cellulose triacetate (CTA). To control the interfacial layer thickness, the surface of the TOCNs was modified by grafting amine-terminated poly(ethylene glycol) (PEG-NH2 ) with different molecular weights. Neat TOCNs or PEG-grafted TOCNs were compounded with CTA to prepare nanocomposite films with different interfacial layer thicknesses. We demonstrated that thinner interfacial layers enhanced the stiffness of the nanocomposite films, whereas thicker interfacial layers enhanced their ductility. The high transparency and low birefringence of the CTA films were preserved even with the addition of TOCNs or PEG-grafted TOCNs. Although the thermal expansion of the nanocomposite films was suppressed by TOCN addition, the presence of PEG layers on the TOCN surfaces had a negative impact on their restraint of the thermal expansion. These results suggest that the interfacial layer thickness plays an important role in the mechanical and thermal properties of nanocellulose-reinforced composites. Graphical abstract: